As forças anti (parentalidades) queer do direito do trabalho: lacunas jurídicas nas garantias parentais a partir da epistemologia materno-subversiva - Lorena Cristina de Araujo Campos (2025)
This research, from a juridical-sociological perspective (Soares; Gustin; Dias; Nicácio, 2020), investigated the labor regulations concerning maternity leave (Art. 392 of the Consolidation of Labor Laws), job security for pregnant employees (Art. 10, item II, letter "b" of the Transitional Constitutional Provisions Act), and paternity leave (art. 7°, item XIX and article 473 of the CLT). The hypothesis put forward is that Labor Law, being based on a heteronormative and binary perspective (which hierarchically characterizes individuals as either male or female), is incapable of protecting subversive forms of parenthood and has anti-queer forces that can either conform or expel them from the formal labor market, effectively suppressing their lived experiences of parenthood. To achieve this, the study utilizes the analysis of queer positionalities, in light of the historical negligence in Brazil of queer legal studies, particularly regarding Labor Law (Ramos, 2020). Similarly, the research aims to understand the social reality of those who care for children within subversive parenthoods and their relationship with the protected labor market (a space that can limit indiscriminate human exploitation, but is not fully reached) (Miraglia, 2009). Queer criticism is a potent method for confronting, at the academic level, the history of heteronormative hegemony with the goal of breaking away from historically oppressive spaces (Butler, 2019). It surpasses the limits and canons of legal thought that are neutral, institutionalized, and closed. For this reason, it can transcend epistemological and social justice issues (Ramos, 2020). Therefore, the research aimed to analyze this process of exclusion and delve into the uncertain ontological spaces of these sexualities, paternities, maternities, and parenthoods that inhabit these incoherent spaces in the lexicon of legitimacy provided by the State (Butler, 2003), to verify which rights are denied within this heterosexual framework of legitimization.